Comparison of Pulmonary Function Tests and Radiological Examinations in Patients with Rheumatoid Arthritis - Murat, Ayse; Kavuncu, Vural; Turgut, Teyfik; Akgun, Murat; Kiris, Adem (Bilimsel Tip Publishing House, 2005)
We investigated estimation of pathologies on thorax high resolution computed tomography (HRCT), previously with clinical findings, pulmonary function tests (PFT) and posterior-anterior chest X-ray findings in patients with rheumatoid arthritis. Forty-five patients (40 females and 5 males) with a mean age of 50.6 +/- 13 years who were diagnosed as rheumatoid arthritis according to the criteria of the American Rheumatism Association were included in the study. After clinical evaluation and Larsen radiological scoring, PFT was applied, posterior-anterior chest X-ray and HRCT were performed. It was detected that for estimation of the pathology on HRCT, posterior-anterior chest X-ray and PFT investigations had high specificity (100%, 100% respectively), but low sensitivity (40%, 21% respectively). According to multivariate analysis, none of the clinical, radiological or PFT evaluations were significant for estimation of pathologic findings on thorax HRCT.
Keywords: rheumatoid arthritis; high resolution computed tomography; pulmonary function tests